Study of Silver Stained Nucleolar Organizing regions (Ag-NORs) applied on cervical smear cytology - Faisal, Ghasak Ghazi; Hussein, Alla'a Ghani (2011)
Worldwide, cervical cancer is the second most common cancer in women (after breast cancer) and is the third leading killer (after breast and lung cancer). Cervical cancer can be detected relatively easily in its premalignant form as it has a relatively long pre-invasive phase and the cervix is easily accessible for direct visualization . The PAP smear is the most popular test used for diagnosis of cervical epithelial lesions, however, due to differential diagnostic difficulties in cytologic al smears , methods are searched for what would be more reliable and would enable exact evaluation of each case. One of these methods is the use of silver stained nucleolar organizer region (Ag +– NOR). Nucleolar organizer regions (NOR) are loops of ribosomal DNA (rDNA) occurring in the nuclei of cells. Cell proliferation under normal physiological conditions is accompanied by increased ribosome biogenesis. The activity of ribosomal genes can be detected using specific markers, the Ag+ nucleolar organizer region (NOR) proteins. The amount of Ag-NOR proteins present during interphase is routinely used to evaluate nucleolar activity and cell proliferation. Thus quantification of Ag-NOR proteins is applied to characterize human cancer cell proliferation ; high levels of Ag-NOR proteins indicate a high rate of proliferation . The aim of this study is to assess the proliferative activity of different cervical lesions ranging from inflammatory lesions (reactive)to LSIL (low grade intraepithelial lesion), HSIL (high grade intraepithelial lesion) and squamous cell carcinoma and to find out whether there is a statistical difference in the mean Ag-NOR count of the different groups of cervical lesions. Fifty cervical smears ,representing the different cervical lesions mentioned, were collected and stained using the Standardized Ag-NOR staining technique . After staining, representative areas in each slide were selected and NORs were counted. The results showed that the lowest mean Ag-NOR count was observed in the benign reactive group(control) =2.07, There is a progressive increase in mean Ag-NOR count with increasing severity of cervical lesion, The highest mean Ag-NOR count belonged to squamous cell carcinoma group (9.02). The results also showed a statistically significant difference among the Ag-NOR counts of the different studied categories . This means that counts of Ag-NOR could be of great diagnostic value for the cytopathologists in conjunction with routine pap stain to evaluate cellular proliferative activity of the lesion and for follow up of patients after treatment to detect regression in the severity of the lesion.